The effect of the shadow economy on the Ukrainian tax system - Holyavko, Anna; Bozhok, Natalia (My University, 2014)
Size of the shadow economy in Ukraine now for some experts estimates exceed more than half of gross domestic product. Expanding the scope of the shadow economy is a real threat to national security. Dynamics and tendencies of development of the shadow economy should be considered in the context of the evolution of economic policy in general. Thus, research on the impact of tax policy at the present stage, as well as its impact on the economic development of the country, is still relevant today.
Keywords: gross domestic product; shadow economy; tax system; податкова система; валовий внутрішній продукт; тіньова економіка; кафедра ділової іноземної мови та міжнародної комунікації